2018
DOI: 10.1371/journal.pone.0200548
|View full text |Cite
|
Sign up to set email alerts
|

Time course of traumatic neuroma development

Abstract: This study was designed to characterize morphologic stages during neuroma development post amputation with an eye toward developing better treatment strategies that intervene before neuromas are fully formed. Right forelimbs of 30 Sprague Dawley rats were amputated and limb stumps were collected at 3, 7, 28, 60 and 90 Days Post Amputation (DPA). Morphology of newly formed nerves and neuromas were assessed via general histology and neurofilament protein antibody staining. Analysis revealed six morphological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 55 publications
1
66
0
Order By: Relevance
“…However, Oliveira et al, studied the time course of neuroma development in rodents and demonstrated that neuroma formation begins as early as 4 weeks postamputation with fully formed neuromas present by 12 weeks. 27 This is consistent with our findings of histological correlates of neuroma formation in the SC group at 12 weeks. Finally, we saw no correlation between axon swirling and optical density scores or between optical density and behavior scores.…”
Section: Figsupporting
confidence: 93%
See 1 more Smart Citation
“…However, Oliveira et al, studied the time course of neuroma development in rodents and demonstrated that neuroma formation begins as early as 4 weeks postamputation with fully formed neuromas present by 12 weeks. 27 This is consistent with our findings of histological correlates of neuroma formation in the SC group at 12 weeks. Finally, we saw no correlation between axon swirling and optical density scores or between optical density and behavior scores.…”
Section: Figsupporting
confidence: 93%
“…The variability in pain response scores before the 12-week timepoint was expected since neuromas typically take at least 12 weeks to form. 27 This behavioral pain response data indicate the Nerve Cap's potential to reduce or eliminate symptomatic neuroma formation-for both the partition and spiral insert designs.…”
Section: Behavioral Pain Responsementioning
confidence: 85%
“…In relation to the probability of occurrence and severity of neuropathic pain and phantom limb symptomatology associated with spare parts surgery techniques, it is important to keep in mind that, when the distance between two severed injured or sectioned nerves is large, axon regeneration and regrowth occurs in an unorganized pattern. If neurorrhaphy of the severed ends is not performed, about 61% of amputee patients report residual limb pain, of which 48.7% are estimated to be caused by a sensitized neuroma [33]. Therefore, the maintenance of nerves in continuity is essential.…”
Section: Discussionmentioning
confidence: 99%
“…The available methods include conservative treatment (opioids and non-opioid analgesic, antidepressants, anticonvulsants), minimally invasive procedure (cryoablation or direct injection of corticosteroid, ethanol, phenol) as well as the total excision. Various alternative methods such as acupuncture, physical therapy, neuromodulation has also been suggested [1][2][3][4].…”
Section: Current Issues In Pharmacy and Medical Sciencesmentioning
confidence: 99%
“…The patient usually reports a focal pain and a tenderness to palpation. The treatment and prevention strategies arer be more successful if targeted at the initial stages of development [3].…”
Section: Introductionmentioning
confidence: 99%